Association between praziquantel treatment and cholangiocarcinoma: a hospital-based matched case–control study. Issue 1 (December 2015) - Kamsa-ard, Supot; Luvira, Vor; Pugkhem, Ake; Luvira, Varisara; Thinkhamrop, Bandit; Suwanrungruang, Krittika; Bhudhisawasdi, Vajarabhongsa
Abstract Background Infection by the liver fluke, Opisthorchis viverrini, remains an important public health problem in Thailand and has resulted in the highest prevalence of infection and incidence of subsequent cholangiocarcinoma (CCA) in the world. Praziquantel (PZQ) is the antihelminthic drug of choice for treatment. Previous studies in hamsters showed that repeated infection and PZQ treatment could increase the risk of CCA. However, the few available epidemiology studies in humans have shown unclear evidence of an increased risk of CCA with frequency of PZQ intake. The present study investigated the relationship between the number of repeated PZQ treatments and CCA. Methods A hospital-based matched case–control study was conducted. All cases and controls were inpatients of a tertiary hospital in Northeast Thailand. During 2012–2014 a total of 210 incident cases of pathologically diagnosed CCA and 840 control subjects were selected from a hospital inpatient database (four controls per case). The four recruited controls were individually matched with CCA cases by gender, age and date of admission. Data were collected in face-to-face interviews using a standardised pre-tested questionnaire. Multivariable conditional logistic regression was used in the analysis of the data. Results The frequencies of PZQ usage among the 210 cases and 840 controls were 48.6 vs. 66.0 for never, 32.9 vs. 24.4 for once, 8.6 vs. 4.9 for twice, and 10.0 % vs. 4.8 % for more than twice, respectively. There was a statistically significant dose–response relationship (p  < 0.001). Compared with subjects who never used PZQ, those who used the medication once, twice, and more than twice were 1.49, 1.82, and 2.30 times more likely to develop CCA (95 % confidence intervals: 1.02 - 2.20, 0.92 - 3.60, and 1.20 - 4.40). These odds ratios (adjusted ORs) had already been adjusted for the effects of eating raw fish, a family history of cancer, and highest educational attainment. Additional PZQ usage increased the odds of developing CCA by 23.0 % (adjusted OR = 1.23; 95 % CI: 1.07 - 1.43). Conclusions The findings show that repeated PZQ treatments are associated with an increased risk of CCA. Paradoxically, this contradicts the common belief that repeated PZQ treatments decrease the risk of CCA. The study also showed a strong association between the number of repeated PZQ treatments and the consumption of raw freshwater fish. This suggests that repeated PZQ treatments may be a surrogate marker of habit of eating raw fish.